Case Report: A Novel PAX3 Mutation Associated With Waardenburg Syndrome Type 1 - Hu, Qiuming; Ma, Huazhong; Shen, Jiawei; Zhuang, Zongming; Li, Jianqiang; Huang, Xinlan; Li, Xian; Li, Haoyu (Frontiers in Genetics, 2021)
Background: Waardenburg Syndrome Type 1 (WS1) is a rare hereditary disease, which is usually caused by the mutations of PAX3 (paired box 3). Here, we reported a pedigree with WS1, which was caused by a novel mutation in PAX3. Case Report: In this present report, a 10-year-old boy and his twin sister from a Han Chinese family presented with iris pigmentary abnormality, synophrys, and broad and high nasal root. Their father presented premature whitening of the hair, but no iris pigmentary abnormality. Their aunts presented the same clinical characteristics with the twins and premature greying of hair. However, none of the patients reported hearing loss. The clinical diagnosis of the four patients from this pedigree was WS1. The whole exome sequencing (WES) revealed a novel mutation (c.959-5T>G) in the PAX3 gene, which could be responsible for the observed pathogenic of WS1 in this pedigree. The genetic test confirmed the diagnosis of WS1 in the four patients from the studied pedigree. Conclusion: This present study demonstrated that genetic test based on WES, an effective alternative to regular clinical examinations, helps diagnose WS1. The newly identified PAX3 gene mutation can expand the understanding of WS1.